Diagnósticos de enfermagem em pacientes transplantados renais de um hospital universitário de Fortaleza-CE - Lira, Ana Luisa Brandão de Carvalho (2005)
The nursing diagnoses identification in renal transplant patients is an adequate and important instrument, because it provides an own nursing language, facilitates the communication between the professional and the patient and defines the nurse competence working scope. This study aimed to analyze the nursing diagnoses distribution presents in renal transplanted patients of an academic hospital of Fortaleza. The population was formed by the renal transplanted who are accompanied in the renal transplant ambulatory of this hospital. It was a cross-sectional study of exploratory and descriptive character. Fifty eight renal transplant patients were evaluated between months of december/04 and april/05. The data collection instruments were: an interview script and a physical exam. The results show the masculine sex predominance, with age average about 40 years, the majority being married, with average about 2 children. The origin was of the countryside cities of the Ceará or of other country states, they had familiar income of four minimum wages on an average, they did not use any contraceptive method. The majority was retired, with low education, catholic, without alcoholic drink and tobacco use. They had a medium duration of 52 dialysis months, mostly the hemodilysis. The most had as renal graft donor a corpse and average six year and half of transplant. Were identified 39 nursing diagnoses, 10 of which above of percentil 75, with the presence of six domains of the 12 investigated. Regarding the associations among nursing diagnoses, we find relation between sleep Pattern disturbed and sexual Dysfunction, sleep Pattern disturbed and ineffective sexuality Patterns, sexual Dysfunction and ineffective sexuality Patterns. In the diagnoses disturbed sensory Perception: visual and disturbed sensory Perception: auditory were found media differences with the age and time of dialysis respectively. The first diagnosis manifested itself in renal transplanted patients with more advanced age. The second diagnosis was present in patients with larger time of dialysis. We realize that the nursing diagnoses study provided us a larger knowledge of these patients’ reality, contributing for a possible implementation of effective nursing actions for the resolution of the identified problems. This can contribute to guide the nursing assistance to the renal transplanted and to provide a better life quality to this clientele.